Pelatihan Pendampingan dan Peningkatan Keterampilan SDM untuk Kemandirian Ekonomi di Perumnas Monang Maning Denpasar Barat - Lia Asmalah; Feb Amni Hayati; Juwita Ramadani Fitria (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This community service activity was conducted to address the need for enhancing the economic capacity and self-reliance of residents in Perumnas Monang Maning, West Denpasar. The objective was to improve the skills and knowledge of local community members in managing economic activities to support sustainable economic independence. The activity took place on October 25–26, 2025, and was led by 10 lecturers from Universitas Pamulang, with 24 community members participating. The program was carried out through material presentations, practical exercises, discussions, and question-and-answer sessions. The implementation followed three stages: preparation, execution, and reporting. During the training, participants actively engaged in hands-on practice and interactive discussions, which enhanced their understanding of economic management, entrepreneurship, and human resource development. The results showed a noticeable improvement in participants’ skills and confidence in applying economic strategies to increase household income and develop community-based initiatives. The activity also strengthened collaboration between the university and the local community, providing a foundation for continued support and guidance. Overall, structured training combined with mentorship effectively empowered residents to achieve economic self-sufficiency.